2016
DOI: 10.1037/pspp0000085
|View full text |Cite
|
Sign up to set email alerts
|

Who cares and who is careless? Insufficient effort responding as a reflection of respondent personality.

Abstract: Insufficient effort responding (IER) to surveys, which occurs when respondents fail to carefully read questionnaire instructions or item content, has recently gained attention as a source of inaccuracy in self-report data (Huang, Curran, Keeney, Poposki, & DeShon, 2012; Johnson, 2005; Maniaci & Rogge, 2014; Meade & Craig, 2012). Whereas previous studies have focused on IER as a methodological nuisance, the current studies examined IER as a substantive variable. Specifically, we hypothesized that IER is a refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(212 citation statements)
references
References 40 publications
17
170
3
2
Order By: Relevance
“…Our results do suggest, however, that sleep problems cannot fully account for the association between alexithymia and symptom over‐reporting. While it is true that tiredness and fatigue may make participants inattentive when they complete questionnaires (Bowling et al ., ) and although we found sleep problems and symptom over‐reporting to be connected with each other, our data speak against sleep‐related inattentiveness as the sole source of symptom over‐reporting. That is, alexithymia was a statistical predictor of symptom over‐reporting over and above sleep problems in the full sample and partial correlations suggested that this was also true in the forensic subsample.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our results do suggest, however, that sleep problems cannot fully account for the association between alexithymia and symptom over‐reporting. While it is true that tiredness and fatigue may make participants inattentive when they complete questionnaires (Bowling et al ., ) and although we found sleep problems and symptom over‐reporting to be connected with each other, our data speak against sleep‐related inattentiveness as the sole source of symptom over‐reporting. That is, alexithymia was a statistical predictor of symptom over‐reporting over and above sleep problems in the full sample and partial correlations suggested that this was also true in the forensic subsample.…”
Section: Discussioncontrasting
confidence: 85%
“…Some researchers (e.g., Hyypp€ a, Lindholm, Kronholm & Lehtinen, 1990) have argued that the inability to verbalize internal sensationsas implicated by alexithymiafosters nocturnal arousal and daytime sleepiness. Daytime sleepiness and fatigue could, in turn, may make people inattentive responders to symptom scales (see, for a discussion of the fatigue hypothesis of inattentive responding: Bowling, Huang, Bragg, Khazon, Liu & Blackmore, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although this is ideal for examining the performance of screening indices, it is not optimal for the purposes of examining the relationship of LQD with other constructs. Emerging research has demonstrated the relationship of LQD with personality, boredom proneness, and aggression (e.g., Bowling et al, 2016;Dunn et al, in press). Other research has demonstrated that response patterns such as differences in responses to positively and negatively worded items or individual susceptibility to data collection method may have predictive value (Chen, Watson, Biderman, & Ghorbani, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Early studies focused nearly exclusively on the development and evaluation of linear composite data screens used to detect random responding on the Minnesota Multiphasic Personality Inventory, a measure consisting of hundreds of dichotomous items used to detect clinical pathologies. Recent work has focused on comparing or categorizing screening techniques for use in survey data (Bowling et al, 2016;Credé, 2010;Huang et al, 2012;Maniaci & Rogge, 2014;Meade & Craig, 2012).…”
mentioning
confidence: 99%
“…Several studies suggest that response validity is related to the personality of the respondent. Among the personality dimensions investigated, those that consistently relate to response validity include conscientiousness, agreeableness, and to a lesser extent, openness to experience (Bowling et al, ; Dunn et al, ; Maniaci and Rogge, ; Ward et al, ). These findings stand to reason given the nature of these personality dimensions (Digman, ; McCrae and Costa, ).…”
Section: Causes Of Response Validitymentioning
confidence: 99%